Experimental combustion an introduction - Mishra, D. P. (Aerospace engineer) (CRC Press, 2014)
This book explains fundamentals essential for carrying out the experiments and analyzing and interpreting the results and, detailed description and methodology of the individual experiments. First part of the book covers fundamentals of combustion, details of instruments used in combustion experiments with end of the chapter worked out examples. The second part of the book deals with individual experiments pertaining to combustion and spray. The objective of conducting the particular experiment is stated clearly with the underlying theory behind it, and the experimental procedure to arrive at the results is given in a practical, pedagogical way. Besides this, all the relevant information about the construction of experimental setup is also discussed extensively.